The Influence of Organizational Climate on Employee Performance: The Mediating Role of Perceived Work Stress - Utami, Made Dwi Mas; Utomo, Kabul Wahyu; Arifin, Andi Harmoko (International Journal of Science and Society, 2024)
This research aims to determine and prove the influence of organizational climate on employee performance. The research was carried out quantitatively, namely using survey methods with specially integrated statistical analysis methods. The questionnaire was a data collection instrument and distributed online via Google Form with a sample size of 211 respondents. The research results obtained are that organizational climate has a significant influence on employee performance. Perceived work stress has a significant influence on employee performance. Organizational climate has a significant influence on perceived work stress and organizational climate has a significant influence on Employee Performance through the mediation of Perceived Work Stress. In an effort to maintain employee performance, we provide space for employees to be able to take certain initiatives in their work as long as their implementation is monitored and in accordance with standard work procedures. Leaders can support and monitor initiatives on a results-oriented basis. support from leaders and policies within the company so that all employees can manage expectations and make these expectations a reality in line with company goals and provide challenging tasks so that employees give their best effort in achieving the assigned tasks.